Real-world data of Azvudine-induced hepatotoxicity among hospitalized COVID-19 patients in China: a retrospective case-control study - Xiong, Yuanguo; Xin, Hao; Shi, Cai; Guo, Xianxi; Chen, Ying; Huang, Caifei; Ma, Fuwang; Yang, Ge; Yang, Jian (Frontiers in Pharmacology, 2025)
BackgroundThe COVID-19 pandemic, caused by the SARS-CoV-2 virus, has led to global health crisis. Although several antiviral drugs have been used to mitigate the severity and mortality of COVID-19, the safety profile remained a critical concern. Azvudine, a new nucleoside analog, has been approved for emergency use in China for COVID-19. However, the incidence and risk factors associated with Azvudine-induced hepatotoxicity in hospitalized patients remained unclear.ObjectsTo assess the prevalence, risk factors, clinical patterns, and outcomes of Azvudine-induced hepatotoxicity by real-world data.MethodsWe conducted a single-center retrospective case-control study at Renmin Hospital of Wuhan University, including patients administered Azvudine for COVID-19 treatment between December 2022 and May 2023. Univariate and multivariate logistic regression analyses were preformed to assess risk factors for Azvudine-associated or -induced hepatotoxicity. Receiver operating characteristic (ROC) curve analysis was performed to calculate the area under the ROC curve (AUC).ResultsIn total, 669 patients were included in the Azvudine-associated hepatotoxicity research. 47.1% patients exhibited hepatotoxicity, abnormal liver function on admission [OR: 5.55 (3.94–7.90), P < 0.001] and antithrombotic drugs [OR: 1.79 (1.27–2.54), P = 0.001] were independent predictors of Azvudine-associated hepatotoxicity, with the area under the ROC curve (AUC) was 0.756 [95% CI: 0.719–0.792, P < 0.001]. Further studies of Azvudine-induced hepatotoxicity revealed 294 cases, of which 27.2% showed hepatotoxicity. The concomitant use of antivirals [OR: 3.80 (1.47–10.1), P = 0.006] and anticoagulant drugs [OR: 3.12 (1.77–5.61), P < 0.001], particularly Ganciclovir [OR: 4.11 (1.45–12.2), P = 0.008], Low-Molecular-Weight Heparin Calcium [OR: 3.00 (1.69–5.33), P < 0.001], and Enoxaparin [OR: 2.68 (0.99–7.10), P = 0.047], were significantly associated with an increased risk of hepatotoxicity. Most hepatotoxicity cases were mild, and recovered or improved after drug withdrawal and treatment, whereas severe cases contributed to the progression of the primary disease and increased mortality risk.ConclusionOur study provided evidence of the significant association between Azvudine and hepatotoxicity in hospitalized COVID-19 patients. These findings underscored the importance of monitoring liver function during Azvudine treatment and caution against concomitant use of certain medications. Further research was warranted to elucidate the mechanisms underlying Azvudine-induced hepatotoxicity and optimize clinical management strategies.